PENGARUH GOOD CORPORATE GOVERNANCE DAN LEVERAGE TERHADAP KINERJA KEUANGAN : Studi Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia - Zahidah, Dipta Aqila; Aris, Muhammad Abdul (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to analyze the effect of good corporate governance and leverage on financial performance. This research method is quantitative. The data collection method in this study uses Documentary Studies and Operational Definitions and Variable Measurements. The population of this study were all LQ45 companies in 2020-2022. The sampling technique for this study was purposive sampling technique. The data analysis technique used in the study used descriptive statistical analysis. The results of this study are that the audit committee variable has no effect on the financial performance variable in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The board of directors variable has an effect on the financial performance variable in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The institutional ownership variable has no effect on the financial performance variable in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The independent board of commissioners variable has an effect on financial performance in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The managerial ownership variable affects the financial performance variable in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022. The leverage variable affects the financial performance variable in LQ45 companies listed on the Indonesia Stock Exchange in 2020-2022